Answer:
I don't know
Step-by-step explanation:
Answer:
x² = 2x - 1
Step-by-step explanation:
x² + 1 = 2x
→ Minus 1 from both sides
x² = 2x - 1
Answer:
The solution is (3,13) and (-1,-3). So none of the mentioned options is correct.
Step-by-step explanation:
Given that
Now, by susbstituting the value of 'y' from equation i to equation ii, we get
Now by factorization, equation iii can be written as
x = 3 and x = -1
By putting the values of x in equation i, we get
y = 4(3) + 1
y = 12 +1
y = 13
and
y = 4(-1) + 1
y = -4 +1
y = -3
Therefore, the solution is (3,13) and (-1,-3). So none of the mentioned options is correct.
Step-by-step explanation:
Q.282 +15% +750
<em><u>282 +15 </u></em><em><u>/</u></em><em><u>1</u></em><em><u>0</u></em><em><u>0</u></em><em><u>+750</u></em>
<em><u>2</u></em><em><u>8</u></em><em><u>2</u></em><em><u>+</u></em><em><u>3</u></em><em><u>/</u></em><em><u>2</u></em><em><u>0</u></em><em><u>+</u></em><em><u>7</u></em><em><u>5</u></em><em><u>0</u></em>
<em><u>1</u></em><em><u>0</u></em><em><u>3</u></em><em><u>2</u></em><em><u>+</u></em><em><u>3</u></em><em><u>/</u></em><em><u>2</u></em><em><u>0</u></em>
<em><u>2</u></em><em><u>0</u></em><em><u>6</u></em><em><u>4</u></em><em><u>3</u></em><em><u>/</u></em><em><u>2</u></em><em><u>0</u></em>